Sacred music by Amandus Ivanschiz: attributions and variants of extant compositions - Jochymczyk, Maciej (Interdisciplinary Studies in Musicology, 2018)
The Pauline father Amandus Ivanschiz (1727-1758) was a composer whose music heralded the style of the early Classical period. He worked mainly in Austria (Wiener Neustadt and Mariatrost), as well as in Rome (it has recently been established that he spent three years there). His sacred music, especially masses, litanies and cantata-style pieces to non-liturgical texts, has been preserved in numerous manuscripts (over 260 items) held in eight countries of Central Europe (Austria, the Czech Republic, Germany, Poland, Slovakia, Slovenia, Switzerland and Hungary). Comparative analysis of all the manuscripts allows one to distinguish several problems commonly encountered in research into eighteenth-century musical sources, such as variants, multiple versions of works and contradictory attributions of authorship, further exacerbated by the lack of originals. This article focusses on the most recent findings relating to Ivanschiz’s life and religious music, as well as discussing and illustrating discrepancies between various copies of the same compositions by reference to selected works. We will also consider the differentiation of authorial variants from variant versions arising from custom.